2014
DOI: 10.1124/dmd.113.056184
|View full text |Cite
|
Sign up to set email alerts
|

Indiplon Is Hydrolyzed by Arylacetamide Deacetylase in Human Liver

Abstract: Human arylacetamide deacetylase (AADAC) catalyzes the hydrolysis of some clinically used drugs, but the information available on its substrates is limited. To increase our knowledge of the AADAC substrates, we examined whether AADAC catalyzes the hydrolysis of indiplon, which was initially developed as a hypnotic sedative drug. It has been reported that approximately 30-40% of the administered indiplon was hydrolyzed to deacetylindiplon in humans, but the enzyme responsible for this hydrolysis had not been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…To estimate the contribution of AADAC, CES1, and CES2 to prasugrel hydrolase activity in HIMs and HLMs, RAF values for each esterase in HIMs and HLMs were calculated (Table 2). We previously demonstrated that indiplon, fenofibrate, and procaine were specifically hydrolyzed by AADAC, CES1, and CES2, respectively (Shimizu et al, 2014a;Fukami et al, 2015). Therefore, we selected these compounds as the specific substrates of each esterase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To estimate the contribution of AADAC, CES1, and CES2 to prasugrel hydrolase activity in HIMs and HLMs, RAF values for each esterase in HIMs and HLMs were calculated (Table 2). We previously demonstrated that indiplon, fenofibrate, and procaine were specifically hydrolyzed by AADAC, CES1, and CES2, respectively (Shimizu et al, 2014a;Fukami et al, 2015). Therefore, we selected these compounds as the specific substrates of each esterase.…”
Section: Resultsmentioning
confidence: 99%
“…Indiplon, Phenacetin, Fenofibrate, and Procaine Hydrolase Activity. Indiplon, phenacetin, fenofibrate, and procaine hydrolase activities were measured according to previous studies (Watanabe et al, 2010;Shimizu et al, 2014a;Fukami et al, 2015). Their substrate concentrations were 1 mM, 5 mM, 25 mM, and 5 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that AADAC is responsible for the hydrolysis of several drugs, such as flutamide (Watanabe et al, 2009), phenacetin (Watanabe et al, 2010), rifamycins (rifampicin, rifabutin, and rifapentine) (Nakajima et al, 2011), and indiplon (Shimizu et al, 2014). AADAC is primarily expressed in the liver and gastrointestinal tract (Watanabe et al, 2009), where it is localized to the endoplasmic reticulum membrane (Frick et al, 2004).…”
Section: Introductionmentioning
confidence: 98%